Analysis and reduction of detailed chemical kinetics mechanisms for combustion of ethanol and air - Pacheco, Augusto Finger (2016)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2016.